(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص: لقد فرضت تغيرات البيئة الاقتصادية كشدة المنافسة وزيادة الاهتمام نحو تعظيم قيمة الزبائن بضرورة تحول المؤسسات نحو تبني نظام التصنيع الرشيق الذي يرتكز على تخفيض تكاليف الإنتاج، وذلك بالاعتماد على أدوات المحاسبة الرشيقة، حيث تهدف هذه الدراسة إلى إبراز دور تبني نظام تكاليف تيار القيمة كأحد أهم أدوات المحاسبة الرشيقة في تخفيض تكاليف التصنيع الرشيق، وذلك بهدف تعزيز الموقع التنافسي للمؤسسات الاقتصادية، والاستجابة للمتطلبات المتنامية للزبائن. لقد توصلت الدراسة إلى أن تبني نظام تكاليف تيار القيمة له دور كبير في تخفيض تكاليف التصنيع الرشيق، وذلك من خلال، استبعاد الأنظمة المعقدة لحساب تكاليف المنتجات، تخفيض مراكز التكلفة، التخلص من الطرق المعقدة لتخصيص التكاليف غير المباشرة، إنتاج تقارير أسبوعية تتضمن معلومات دقيقة وملائمة حول رقابة التكاليف، وتشجيع العاملين على استخدام مقاييس الأداء المرئية. كلمات دالة: تفكير رشيق، تصنيع رشيق، محاسبة رشيقة، نظام تكاليف تيار قيمة Abstract: The Changes In The Economic Environment, Such As The Intensity Of Competition And The Increase In Interest Towards Maximizing The Value Of Customers, Have Imposed The Necessity For Enterprises To Shift Towards Adopting A Lean Manufacturing System That Is Based On Reducing Production Costs, By Relying On Lean Accounting Tools, As This Study Aims To Highlight The Role Of Adopting The Value Stream Cost System As One Of The Most Important Tools Lean Accounting In Reducing Lean Manufacturing Costs, With The Aim Of Enhancing The Competitive Position Of Economic Enterprises And Responding To The Growing Requirements Of Customers. The Study Found That Adopting A Value Stream Costing System Has A Major Role In Reducing Lean Manufacturing Costs, By Excluding Complex Systems For Calculating Product Costs, Reducing Cost Centers, Eliminating Complex Methods Of Allocating Indirect Costs, Producing Weekly Reports That Include Accurate And Appropriate Information About Cost Control, And Encouraging Employees To Use Visual Performance Measures. Key Words: Lean Thinking, Lean Manufacturing, Lean Accounting, Value Stream Costing System